Erosão na microbacia do arroio Sarandi: voçoroca do Buraco Fundo, Santa Maria/RS - Avila, Luciele Oliveira de (2009)
The microbasin of the Sarandi little stream, that it crosses the cities of Saint Maria and Dilermando de Aguiar, situated in the State of Rio Grande do Sul, south region of Brazil, presents innumerable erosions; the most significant soil erosion on that region is well known as Buraco Fundo gully, which is also our case of study. The general goal of this dissertation was to delimitate and to characterize the geological and geotechnical materials of that soil erosion, in order to understand the parameters that influence that erosive process. As specific goals tries to evaluate the erosive marks and the pseudo-karstic relief, as well as the degree of erodibility of that materials, in order to minimize its advance. Nevertheless, this writing involved theoretical research, fieldwork and laboratory, where the assays of geotechnical characterization and direct and indirect evaluation of erodibility had been executed. The soil erosion of the Buraco Fundo gully occurs in sedimentary rocks according to direction N20º-35ºE. It results of rotational slippings and pseudo-dolines that evaluates to ridges and ravines. It was assayed the superficial horizon (A/B) and the sandstone layer located in the amphitheater of that soil erosion. The horizon A/B presents an arenaceous and argillaceous texture, plastic behavior and the biggest quotient of emptiness, while the sandstone did not present plasticity. The coefficient of sorption(s) was bigger in the sandstone than in the superficial horizon. Therefore, it can be foreseen that the saturation in rainy events is faster in the sandstone than in the superficial horizon. The sandstone makes the material, after the saturation, establish the superficial draining. It occurs, as consequence, the carry of fine materials. It was verified a direct relationship between the results of the slaking test and the assays of infiltrability. The sandstone showed high desagregation and high coefficient of infiltrability. The values of Pi/s had been superior to 50, for both samples; they were classified as erodible according to Nogami and Villibor (1979). The coefficient of erodibility (k) was 10 times bigger in the sandstone, which can be related to the loss of resistance due to suction and the apparent fragility of the cementing agent. The soil revealed to be very resistant cause presents organic matter , roots and fines. The results indicate the necessity of protection of this area since the initial period of erosion, in order to avoid that process of erosion reaches the rock.